Comparison of Planar, Pinhole and SPECT CT Imaging in Dual Phase 99m Tc-Sestamibi Parathyroid Scintigraphy - Canbaz, F.; Sahin, Z.; Akpinar, S. (Springer, 2012)
…
25th Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 27-31, 2012 -- Milan, ITALY